Perspectives and Trends in Foreign Language Policies in China: The Case of Portuguese - Reis Jatobá, Júlio (Íkala, Revista de Lenguaje y Cultura, 2024)
This case study aims to provide a review of language policies pertaining to foreign language teaching in China through the lens of China’s geopolitical position and its self-perception as one of the leaders and most active actors in developing South-South cooperation. From an initial study of 127 academic materials, documents, and news articles containing explicit or implicit references to policies, initiatives, or proposals related to the development and planning of less commonly taught foreign languages —Portuguese among them— at the tertiary level, 35 sources were selected for further analysis of the relationship between foreign language education and China’s foreign policy. These sources shed light on the multifaceted nature of language policies in China, particularly in relation to foreign language teaching. Ultimately, this analysis seeks to identify patterns, developments, and implications for China’s foreign language instruction approach.